PS01.041: REMOVAL OF ESOPHAGEAL HEMANGIOMA USING ENDOSCOPIC SUBMUCOSAL DISSECTION: A CASE REPORT AND REVIEW. (14th September 2018) - Tani, Yukiko; Nakajima, Masanobu; Muroi, Hiroto; Fujita, Junki
Abstract: Background: Esophageal hemangiomas are rare, representing around 3% of all benign esophageal tumors. Esophagectomy or tumor enucleation has been performed to treat esophageal hemangiomas, but recently the use of endoscopic therapy, such as endoscopic mucosal resection or endoscopic injection sclerotherapy, is increasing. We describe removal of a hemangioma using endoscopic submucosal dissection. Methods: A 59-year-old woman underwent endoscopic examination after an esophageal lesion was found during a general health examination. Endoscopy identified a broad-based, elevated, dark purple lesion located 17 cm distal from the incisor teeth. It measured approximately 25 mm and was rounded and soft.Endoscopic ultrasonography using a 20-MHz catheter probe and the water filling method identified a tumor 25 mm in diameter located in the mucosal and submucosal layers. The border was unclear, but the bottom of the tumor was demarcated from the adjacent normal muscle layer. Compared with the adjacent muscle layer, the tumor was hyperechoic. On the basis of these endoscopic findings, the lesion was diagnosed as a hemangioma. Because the tumor was broad-based and relatively large, we thought that polypectomy or EMR should be avoided to prevent incomplete resection and postoperative hemorrhage from the residual stump. We therefore decided that ESD was the best treatment modality for this lesion. Results: Approximately 2 mL of the solution was injected into the submucosal layer at intervals, which was repeated until the mucosa became elevated. After lifting the lesion, the mucosa including the tumor was gently cut with the Flush knife using the Endocut mode. The submucosal layer was highly fibrous, so lifting the lesion was somewhat difficult. The histopathological findings showed formation of a vascular lumen with irregular dilatation just below the lamina muscularis mucosa, suggesting a cavernous hemangioma. The patient was discharged 5 days after surgery without complications. Conclusion: Until quite recently, large or broad-based esophageal hemangiomas had been treated by esophagectomy or sclerotherapy. Esophagectomy is associated with a high mortality rate [19], and endoscopic sclerotherapy may cause hemorrhage upon puncture, side effects due to the infused agents, and other complications. Endoscopic resection is less invasive than sclerotherapy, and further advances in endoscopic treatment and instruments may reduce the risk of several complications. ESD has being established as a safer, less invasive therapy than esophagectomy, it is perhaps the best therapeutic option for treating large or broad-based submucosal esophageal hemangiomas. Disclosure: All authors have declared no conflicts of interest.